2010
DOI: 10.1002/ejoc.201000592
|View full text |Cite
|
Sign up to set email alerts
|

Planar Chiral Flavinium Salts – Prospective Catalysts for Enantioselective Sulfoxidation Reactions

Abstract: A novel planar chiral flavinium salt, 3-benzyl-5-ethyl-10-(8-phenylnaphthalen-1-yl)isoalloxazinium perchlorate (2b), which bears a phenyl cap that covers one side of the isoalloxazinium skeleton plane, has been prepared as a potential catalyst for the enantioselective H 2 O 2 oxidation of sulfides. The rate of H 2 O 2 oxidation of sulfides in the presence of racemic 2b is comparable to that of the reaction catalysed by 5-ethyl-3,10-dimethylisoalloxazinium perchlorate, which indicates that the bulky shielding s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
42
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 61 publications
4
42
0
Order By: Relevance
“…The starting materials methylurea, malonic acid, and acetic anhydride were reacted in one‐pot to give the pyrimidinetrione 8 with over 80% yield . This compound was then chlorinated by phosphorus oxychloride, catalyzed by a small amount of water, to obtain the pyrimidinedione 9 with 81% yield . Compound 9 was refluxed with methylhydrazine in ethanol to give the hydrazinylpyrimidinedione 10 with 65% yield after isolation.…”
Section: Resultsmentioning
confidence: 99%
“…The starting materials methylurea, malonic acid, and acetic anhydride were reacted in one‐pot to give the pyrimidinetrione 8 with over 80% yield . This compound was then chlorinated by phosphorus oxychloride, catalyzed by a small amount of water, to obtain the pyrimidinedione 9 with 81% yield . Compound 9 was refluxed with methylhydrazine in ethanol to give the hydrazinylpyrimidinedione 10 with 65% yield after isolation.…”
Section: Resultsmentioning
confidence: 99%
“…The flavinium salt was proposed to be converted, by means of hydrogen peroxide, to a chiral flavinium hydroperoxide able to oxidize methyl aryl sulfides in enantioselective manner (Scheme ). A different flavinium salt, 3‐benzyl‐5‐ethyl‐10‐(8‐phenylnaphthalen‐1‐yl)isoalloxazinium perchlorate 26 , featuring a phenyl cap able to shield one side of the isoalloxazinium plane, was recently synthesized by Cibulka and coworkers 73. This organocatalyst was found to promote the enantioselective oxidation of alkyl aryl sulfides in the presence of hydrogen peroxide affording the sulfoxides with modest ee values (Scheme ).…”
Section: Oxidation Of Sulfides To Sulfoxidesmentioning
confidence: 99%
“…Although isoalloxazinium and alloxazinium salts are important organocatalysts for sulfoxidations with hydrogen peroxide and several studies of their catalytic activity have been published [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29], there has been no direct comparison of their efficiency under the same reaction conditions. Only individual comparative studies for both groups of flavinium salts have been reported.…”
Section: Introductionmentioning
confidence: 98%
“…This method is highly chemoselective, producing sulfoxides with no over-oxidation to sulfones [2,[13][14][15][16][17][18][19][20][21][22][23][24]. If a chiral flavinium salt is employed, the sulfoxidation proceeds with high enantioselectivity [25][26][27][28][29]. Flavin-cyclodextrin conjugates are the most efficient metal-free catalysts reported so far, reaching enantioselectivities up to 80% ee for aromatic and 91% ee for aliphatic sulfides [28,29].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation